Social Work Students’ Challenges in Flexible Learning and Implications for Social Work Education: A Study in Bicol, Philippines - Uclaray, Angelo; Magdasoc, Thea Mari; Noora, Andrea Joyce; Sales, Ma. Vida Teresa (Asean Social Work Journal, 2023)
Social work students encountered different challenges as they experience online and distance learning during the COVID-19 pandemic. Significantly, examining the learners’ situations can contribute in obtaining evidence-based knowledge useful in enhancing academic policies and practices. Hence, this study investigated on the personal, institutional, learning environment, and technological challenges of social work students when flexible learning was implemented. It sought to discuss policy implications for social work education. The study captured 296 respondents in one university in the Bicol Region, Philippines. The researcher-made survey questionnaire used in the study obtained a coefficient of a=0.92, which means that the whole scale's reliability estimate was highly acceptable. The instrument was in Google Forms and distributed to the respondents online. The collected data were subjected to descriptive statistics for interpretation and analysis. The results revealed that the frequently encountered challenges were: having to fulfill home and school responsibilities simultaneously, overlapping activities/tasks from two or more subjects, power interruptions, and having an unstable mobile data connection. Therefore, the academic community, including the administrators, student organizations, faculty members, and all equally essential stakeholders can address the identified challenges through policy enhancement and partnership building with organizations and companies offering technology-related services.